[Unknown]
Austria, travelling with car among mountains, Wien, old VW, trabant, different cars, walking on the street, Moscow, monuments, big traffic, lake & town among mountains (Switzerland?), Venice, Italy, procession on the street in different traditional costume, mountains, stream, Cracow(?), Balaton, sailing-boat, slide,